1984
DOI: 10.1021/bi00303a003
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of brain .alpha.-actinin. Its characterization and a comparison of its properties with those of muscle .alpha.-actinins

Abstract: A rapid purification procedure has been developed for the isolation of alpha-actinin from chicken brain. Brains were homogenized in cold water containing 0.5 mM phenylmethanesulfonyl fluoride (PMSF), the homogenate was centrifuged, and the alpha-actinin was extracted from the pelleted material in a low ionic strength buffer for 30 min at 22 degrees C. Purification of the protein to homogeneity on sodium dodecyl sulfate containing polyacrylamide gels required an ammonium sulfate precipitation step followed by c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
38
0

Year Published

1985
1985
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(39 citation statements)
references
References 59 publications
(66 reference statements)
1
38
0
Order By: Relevance
“…The binding ratio is approximately 1 molecule of x-actinin (aa, bb or cc) per 9 -11 actin units in the actin filament. This binding ratio seems to be quite general since several authors reported similar ratios despite the Pact that they used different methods, different temperatures and they studied the interaction between muscle actin and various x-actinins from skeletal muscle [3, 281, Ehrlich tumor cells [29], brain [30] or macrophages [31].…”
Section: Stoichiometry Qf the A-actinin/f-actin Inteructionmentioning
confidence: 95%
“…The binding ratio is approximately 1 molecule of x-actinin (aa, bb or cc) per 9 -11 actin units in the actin filament. This binding ratio seems to be quite general since several authors reported similar ratios despite the Pact that they used different methods, different temperatures and they studied the interaction between muscle actin and various x-actinins from skeletal muscle [3, 281, Ehrlich tumor cells [29], brain [30] or macrophages [31].…”
Section: Stoichiometry Qf the A-actinin/f-actin Inteructionmentioning
confidence: 95%
“…However, the significance of this spacer region is unclear, and it is notably absent from D. discoideum a-actinin which is considered to be the archetypal non-muscle isoform (Noegel et al, 1987). Finally, non-muscle a-actinins are calcium sensitive with respect to binding F-actin, whereas muscle isoforms are calcium insensitive (Burrdige and Feramisco, 1981;Bennett et al, 1984;Duhaiman and Bamburg, 1984;Landon et al, 1985). EF-hand calcium-binding domains contain a helix-loop-helix motif, where coordination of the calcium ion is dependent on the residues at the X, Y, Z, -X, -Y and -Z vertices in the loop.…”
Section: Sk Dfrasenhfd~esdnlhsdefkaclislgqvgndlqtgeaefarimslvdpngqgtmentioning
confidence: 99%
“…in the presence of Ca2+, whereas the smooth-muscle and skeletal-muscle isoforms are CaZ + insensitive (Burrdige and Feramisco, 1981;Bennett et al, 1984;Duhaiman and Bamburg, 1984;Landon et al, 1985). The smooth-muscle and non-muscle isoforms of a-actinin arise by alternative splicing of the transcript from a single gene (Arimura et al, 1988;Waites et al, 1992).…”
mentioning
confidence: 99%
“…The only functional difference detected thus far between s-␣-actinin and non-s-␣-actinin is that binding of the former to actin is Ca 2Ï© insensitive, whereas binding of the latter is Ca 2Ï© sensitive [Burridge and Feramisco, 1980;Duhaiman and Bamburg, 1984;Bennett et al, 1984;Landon et al, 1985]. Thus, fluorescently labeled non-s-␣-actinin injected into fibroblasts is selectively and rapidly incorporated into preexisting dense bodies along stress fibers and into focal adhesion plaques [Feramisco, 1979;McKenna et al, 1985;Pavalko and Burridge, 1991].…”
Section: Introductionmentioning
confidence: 99%